Cartel Problems: Comment - Mills, David E.; Elzinga, Kenneth G. (American Economic Review, 1978)
In a recent paper in this Review, Dale Osborne poses four internal faced by cartels. The (of the contract surface) and together pertain to the determination of an optimal collusive policy; the and pertain to firms' incentives to unilaterally cheat on that policy. Claiming Standard theory teaches us that cartels are inherently unstable, mainly because of the sharing and deterring problems (p. 835), Osborne proceeds to argue that these are readily solved so that only the locating and detecting remain as obstacles to internal cartel stability. Quite apart from his treatment and purported resolution of the sharing and deterring problems, which provide the focus for this comment, there is some question as to whether or not Osborne correctly interprets theory. It would appear he does not. In particular his argument that economic orthodoxy stresses the deterring problem is misplaced; in fact it is the detecting problem that is generally emphasized. For example in his treatise on monopoly, Donald Dewey (p. 19) indicates the importance to a cartel's success of reliable information on the behavior of member firms. The information is necessary, Dewey claims, to detect cheaters. In a recent volume on antitrust law, Richard Posner writes, Cheating is presumably least likely when detection is prompt and certain... (p. 53, emphasis added). George Stigler certainly emphasizes the detecting problem over the problem of deterrence; indeed he does not view deterring per se as a problem: Once detected, the deviations [i.e., cheating] will tend to disappear because they are no longer secret and will be matched by fellow conspirators if they are not withdrawn (p. 42). Osborne's exegesis of standard theory is incomplete. Detection is a serious and widely recognized problem that has been emphasized more than deterrence.' Questions of economic literature aside, even if deterring is to be granted equal status with detecting as a cartel its importance depends crucially on the extent of the detecting problem. As we shall show, Osborne's purported resolution of the deterring problem is either ineffectual or unnecessary depending on the status of the detecting problem. If the cartel has a detecting problem, then his resolution of the deterring problem breaks down. If detecting is not a problem for the cartel, then following Stigler, neither is deterring, since detection alone is sufficient to bring an end to cheating. Moreover if deterring persists as a problem, as Osborne seems to aver, even when there is no detecting problem, his resolution of it is not strictly superior to an infinite number of alternative resolutions. We also argue that Osborne's resolution of the sharing problem, although correct in the case of a single joint profit-maximizing point, is unconvincing for the case of multiple joint profit-maximizing points. Finally, in spite of its failure as a final and complete resolution of the deterring problem, Osborne's quota rule has some interesting implications for still another (domestic) cartel problem: the avoidance of antitrust prosecution and conviction.